Efficacy and tolerability of short contact therapy with tretinoin, clindamycin, and glycolic acid gel in acne: A randomized, controlled, assessor‐blinded two‐center trial: The MASCOTTE study. Issue 1 (6th January 2021) - Bertolani, Maria Beatrice; Rodighiero, Eleonora; Gandolfi, Marco; Lotti, Torello; Pedrazzi, Giuseppe; Puviani, Mario; Milani, Massimo; Feliciani, Claudio; Satolli, Francesca
Abstract: Retinoids and antibiotics topical treatments are commonly used as first line therapy in mild to moderate acne. However, irritant contact dermatitis is a common side effect of topical retinoids. A strategy to increase local tolerability is the "short contact therapy" (SCT) approach, consisting in the application of the product with the complete removal after 30 to 60 minutes using a non‐aggressive cleanser. A gel containing tretinoin 0.02%, clindamycin 0.8%, and glycolic acid 4% in polyvinyl alcohol (MP‐gel) has shown to be effective as monotherapy in mild to moderate acne with a tolerability profile similar to other topical retinoids. So far, no trials have been performed with this gel comparing the tolerability profile of SCT with standard application therapy (SAT). We conducted a 2‐center randomized parallel groups, controlled, assessor‐blinded study, comparing MP‐gel applied as SCT in comparison with MP‐gel used as SAT (The "MASCOTTE" trial). Forty‐six subjects (nine men and 37 women, mean age 23 ± 4 years, range 18‐31 years) with mild‐to‐moderate acne were enrolled, after their written informed consent in a randomized, parallel groups controlled, assessor‐blinded 8‐week trial. Twenty‐three were assigned to MP‐gel once daily (evening application) using the SCT approach (ie, complete removal of product after 1 hour using a gentle cleanser), and 23 were randomized to the SAT approach with the same gel. The primary endpoint was the evolution of the tolerability score (TS) assessed evaluating four items: erythema, dryness, stinging, and burning, using a 4‐point score scale (from 0: no symptom to 3: severe symptom). Secondary endpoints were the evolution of global acne grading system (GAGS) score (range: from 0 to >39) and the investigator global assessment (IGA of acne severity) score (range from 0 to 4). TS was evaluated at 2, 4, and 8 weeks. GAGS and IGA scores were evaluated at baseline and at week eight. At week eight, an efficacy global score (EGS) (from 1: no efficacy to 4: very good efficacy) and a tolerability global score (TGS) (from 1: very low tolerability to 3: very good tolerability) evaluation were also done. All the evaluations were performed by an investigator unaware of treatment groups allocation (SCT or SAT). Thirty‐eight subjects (83%) completed the 8‐week treatment period. Eight subjects (two in the SCT group and six in the SAT group) dropped out prematurely due to low skin tolerability. In the SCT the TS at week two was 1.3 ± 1.7, in the SAT group TS was significantly higher (3.1 ± 1.7) ( P = .028). TS was significantly lower in SCT group vs SAT also at weeks four and eight ( P = .01; ANOVA test). The GAGS score at baseline was 19 ± 7 in the SCT group and 23 ± 4 in the SAT group (NS). At week 8 the GAGS score in SCT was significantly reduced to 8.5 ± 2.8 (−55%) ( P = .001 vs baseline) and was also significantly lower in comparison with SAT group (8.5 vs 15; P = .0054). The IGA scores at baseline were 1.9 ± 0.6 in SCT and 2.4 ± 0.7 in SAT group. At week eight, in comparison with baseline values IGA score was reduced significantly by 48% in SCT and by 30% in SAT. EGS and TGS were significantly higher (better clinical efficacy and better tolerability) in SCT in comparison with SAT (3.6 ± 0.5 and 2.9 ± 0.3 vs 2.7 ± 0.6 and 1.5 ± 0.7; respectively). This tretinoin, clindamycin, glycolic acid gel, applied as SCT, has shown a better skin tolerability and at least a comparable clinical efficacy in comparison with the standard application modality in the treatment of mild‐to‐moderate acne. The SCT therefore could be an effective treatment strategy which could improve subjects' compliance and adherence.